Learning Strategy of Pancasila and Citizenship Education on Students’ Character Development (Journal of Primary Education, 2020)
This study aimed to analyze and describe the characters that can be developed in Pancasila and citizenship education. The research method used descriptive qualitative with a phenomenological design. The research subjects were the principal, teachers, and students. data analysis used Miles and Huberman, namely data collection, data reduction, display data and conclusions or verification. The results of the research showed that the learning implementation strategy of the Pancasila and citizenship education through habituation, communication, and role models which can develop religious, nationalist, independent, cooperation and integrity characters was very well in every process of teaching and learning in the classroom. Supporting and inhibiting factors in the implementation of Pancasila and citizenship education with character development include; supporting factors due to the existence of learning tools, the cooperation of the teacher component, the existence of student independence in every teaching and learning activity. The inhibiting factor was due to a number of learning tools could not provided in learning, many students in the classroom can hamper the process of teaching and learning activities in classroom.